An investigation in the effects behind the increase in cases of domestic violence in urban Zimbabwe: the case of Gweru urban between the periods of 2008 to 2014. - Marisa, Douglas J. (Midlands State University, 2017)
The research study investigates the nature of domestic violence and the reasons for the continuous increase in Gweru urban. The study focused on the lived experiences among the victims of domestic violence. Factors noted causing the increase of domestic violence are misinterpretations of equal rights and Domestic Violence Act, the patriarchal systems, cultural norms and also the adverse economic situation in the country. It examines the effects of domestic violence on socio-economic development were the mental and physical capabilities of victims negatively affect the productivity thus, gross domestic product(GDP) and increase the national budget. Diversion of funds from development programs is used for health care by the employer. It covers the experiences, perceptions of violence held and the coping strategies adopted by the victims. Qualitative and quantitative methods were used to gather valid and reliable data, these included perusal of records, questionnaires, in-depth interviews from officials and observations. The research findings confirmed the existence of domestic violence amongst the intimate partners. Various recommendations were suggested which include the need for incorporation of the rights of men in the constitution, awareness campaigns on what constitutes equal rights and Domestic Violence Act.